THE TRIAL OF JESUS - Eltjo JH Schrage (Obiter, 2022)
The trial and subsequent crucifixion of Jesus Christ have given rise to one of the great religions of the world, inspired numerous works of art and music and even epic films. These events have also been the subject of legal historians. This article examines Jesus‟ trial from a procedural point of view and questions whether it conformed to the procedural requirements which were in force at the beginning of the first millennium. It appears as if justice may not have been done.